Pengaruh Pendidikan dan Pelatihan, Inovasi Personel, Orientasi Pelayanan, dan Sistem Reward Punishment terhadap Implementasi Reformasi Polri - Earlyanti, Novi Indah; Syafruddin, Syafruddin (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of education and training, personnel innovation, service orientation, and reward-punishment system on the implementation of reform in the Indonesian National Police (Polri). Institutional transformation requires strengthening the capacity of officers through systematic education and training, fostering innovation in policing tasks, focusing on public service orientation, and implementing fair reward and punishment mechanisms. The study employs a literature review method, reviewing 50 scholarly articles, national and international journals, and official Polri reports over the last ten years (2015–2025). The findings indicate that continuous education and training enhance technical and managerial competence, while personnel innovation promotes creativity and operational efficiency. Service orientation reinforces an organizational culture that is responsive to public needs, and the reward-punishment system ensures compliance with procedural and ethical standards. The integration of these four variables contributes significantly to the success of reform implementation. The literature emphasizes the need for education planning based on organizational needs, fostering operational innovation, enhancing service orientation, and applying a transparent and fair reward-punishment system. These findings provide a foundation for policymakers to design more effective, adaptive, and sustainable reform strategies, improving professionalism, accountability, and public trust in the institution.